Undrained uplift resistance of under-reamed open caisson shafts - Sheil, BB; Templeman, JO; Orazalin, Z; Phillips, BM; Song, G (ICE Publishing, 2023)
Deep, large-diameter caisson shafts are a popular means of constructing underground storage and attenuation tanks and pumping stations for the water and wastewater industry. One of the key design concerns for these structures is resistance to flotation during periods when the tanks are only partially filled or empty. In this paper, two-dimensional numerical analysis is used to explore the undrained uplift resistance provided by under-reaming the walls of the caisson shaft to create an enlarged base. The primary aim of the study is to assess the influence of the taper angle of the anchor (i.e. the protruded base) on the resulting uplift resistance. The effects of the anchor–soil interface roughness factor, soil weight, surcharge pressure and caisson radius are also investigated. The results indicate that the effect of the taper angle on both the uplift bearing capacity and the developed horizontal reaction can be very significant. The numerical output informs the development of a closed-form approach for application in routine design. The new design method is shown to provide an excellent agreement with both finite-element and additional finite-element limit analysis calculations. By way of example, the proposed design method is applied to a hypothetical design scenario.